2019
DOI: 10.1016/j.jid.2018.08.022
|View full text |Cite
|
Sign up to set email alerts
|

Dermal CD207-Negative Migratory Dendritic Cells Are Fully Competent to Prime Protective, Skin Homing Cytotoxic T-Lymphocyte Responses

Abstract: Dendritic cells (DCs) are important inducers and regulators of T-cell responses. They are able to activate and modulate the differentiation of CD4 þ and CD8 þ T cells. In the skin, there are at least five phenotypically distinct DC subpopulations that can be distinguished by differential expression of the cell surface markers CD207, CD103, and CD11b. Previous studies have suggested that dermal CD11b À CD207 þ conventional type 1 DCs are indispensable for the priming of a skin homing cytotoxic T-lymphocyte resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…After demonstrating the superior induction of specific T cell responses by DIVA in the primary immune response phase, we evaluated the biological efficacy of this vaccination scheme in a virus infection model. We chose the vaccinia virus (VV-OVA) model, as we have recently demonstrated that CTL primed by skin DCs are highly effective in protecting against a challenge at a distant site 25 . Female mice were treated as indicated in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After demonstrating the superior induction of specific T cell responses by DIVA in the primary immune response phase, we evaluated the biological efficacy of this vaccination scheme in a virus infection model. We chose the vaccinia virus (VV-OVA) model, as we have recently demonstrated that CTL primed by skin DCs are highly effective in protecting against a challenge at a distant site 25 . Female mice were treated as indicated in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…VV-OVA (2 × 10 6 PFU) infection was performed on day 7 days after TCI by i.p. injection 25 . Briefly, 5 days post infection, ovaries were collected, and homogenates seeded on monolayers of BSC-40 fibroblasts in serial dilutions to determine PFU 48–72 h later.…”
Section: Methodsmentioning
confidence: 99%
“…Dendritic cells that reside in the dermis are known as dermal dendritic cells (dDCs). In a similar manner to LCs, dDCs migrate to the lymph nodes, and are professional antigen-presenting cells efficient at priming adaptive immune responses [117,118]. It was recently shown that dDCs can induce tolerance to topically applied antigens encountered in the hair follicles [119].…”
Section: The Skin As An Immune Organmentioning
confidence: 99%
“…Using a contact sensitizer hapten, a protein, and a virus, a generation of TRMs in the skin after repetitive antigenic challenges could be observed [72]. Dendritic cells are also able to prime the creation of TRMs in inflamed murine skin [106]. Another study using a contact protein showed that TRMs as well as their local increase following antigen exposure are important for sufficient control of hypersensitivity responses [43].…”
Section: Othersmentioning
confidence: 99%